Living in the Beautiful City: Everyday Racism in East-Central Europe - Rodríguez Polo, Mario (Lidé města, 2018)
This paper presents a view of a Central European city as a space where memory processes provide the context for understanding everyday racism. Participatory research gave voice to otherwise muted experiences of constructed “others” living in the Beautiful City as they navigate and experience racism. Their experiences under the disciplinary gazes of those constructed as a hegemonic population and its occasional violent aggressions give account of how the urban space remains an essential part of a mechanism of subjugation for visible “others”. The hegemonic population perceives urban space as neutral, considering racism a marginal or an accidental phenomenon. On the contrary; the analysed experiences are only possible to explain under the hidden existence of a racial hierarchy, based on the locals’ performed right of belonging to the city. Such a hidden hierarchy constitutes a key element for understanding racism in East-Central Europe.